REDUCING ADMINISTRATIVE FRICTION TO ENHANCE PUBLIC SERVICE EFFECTIVENESS THE MEDIATING ROLE OF CITIZEN TRUST (IC-BESTS: International Conference on Business, Economics, Technology, and Social Sciences, 2026)
The rapid expansion of digital public services has transformed the way governments interact with citizens. However, digitalization does not automatically improve public service effectiveness, as citizens may still encounter administrative burdens that hinder service accessibility and reduce trust in public institutions. This study examines the effect of Administrative Burden on Public Service Effectiveness through the mediating role of Citizen Trust in the context of digital public services provided by the Makassar City Government, Indonesia. A quantitative explanatory design was employed using data collected from citizens who had utilized digital public services. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM), complemented by PLS-Predict and Importance–Performance Map Analysis (IPMA). The results reveal that Administrative Burden significantly influences Citizen Trust (β = 0.599, p < 0.001), while Citizen Trust has a strong positive effect on Public Service Effectiveness (β = 0.703, p < 0.001). Furthermore, Citizen Trust significantly mediates the relationship between Administrative Burden and Public Service Effectiveness (β = 0.422, p < 0.001). PLS-Predict indicates moderate predictive power, confirming the model's ability to predict out-of-sample observations. IPMA further identifies Citizen Trust as the most important leverage factor for improving Public Service Effectiveness, exceeding the contribution of Administrative Burden. The study extends Administrative Burden Theory into the context of digital local government services by demonstrating that administrative simplification enhances public service effectiveness primarily through strengthening citizen trust. These findings suggest that digital public service reform should prioritize reducing administrative friction while simultaneously fostering transparency, procedural fairness, responsiveness, and institutional trust to achieve sustainable improvements in public service effectiveness.